Level of Airbone Toluene in Work Environment is Associated With Level of Urine Hippuric Acid in Printing Workers at Rungkut Surabaya - Fardani Irmasari (Universitas Airlangga, 2018)
One of industrial hazards in printing can come from chemical elements. The chemicals that may be in the printing industry is toluene. Toluene used in 75% of printing work activity. The biggest toluen used as automatic cleaning. Other toluen used as a printing ink, solvent, varnish and glue. The purpose of this study was to analyze the relationship between airbone toluene levels with hippuric acid in workers Printing in Rungkut Surabaya. This research was an observational analytic, used cross sectional design. The sample of this study were 30 people, taken by random sampling. The results of pearson correlation test showed that there were a association between airbone toluene with hippuric acid in urine (p= 0.000; r=0.796) and results of pearson correlation test showed thatthere is no association between airbone toluene with eye irritation complaint (p=0.268). Its conclued that level of airbone toluene in work environment is associated with level of urine hippuric acid in printing workers at Rungkut Surabaya. Suggestions from this research is the company must conduct periodic monitoring in the airbone workplace of workers and to raise workers awareness of the importance of PPE.